Perkembangan Pemikiran Wakaf Asuransi Syariah di Indonesia - Munandar, Eris (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2021)
Background. The development of the sharia economy opens up opportunities for sharia financial instruments, one of which is sharia insurance to become an object that can be waqf. This prompted DSN-MUI to issue fatwa 106/DSN-MUI/X/2016 concerning waqf insurance benefits and investment benefits.Aim. The purpose of writing this paper is to explore the development of Islamic insurance waqf thinking in Indonesia, more precisely to examine some of the literature that has examined Islamic insurance waqf as the object of study.Methods. The method used in this research is literature review with a qualitative approach.Results. This paper explain that the DSN-MUI fatwa no. 106/DSN-MUI/X/2016 which is the legal basis for the development of waqf thinking using sharia insurance instruments, its legal status is allowed because it refers to the principle of maslahah mursalah. The waqf referred to in the fatwa is an insurance benefit waqf whose provisions are set for no more than 45% of the total benefits obtained, while investment benefits of no more than 1/3 of the maximum amount of wealth may be waqf on investment benefits with a note with the approval of the heirs.